2010
DOI: 10.3109/10826084.2010.528123
|View full text |Cite
|
Sign up to set email alerts
|

P3a Amplitude Predicts Successful Treatment Program Completion in Substance-Dependent Individuals

Abstract: This study examined P3a amplitude as a direct predictor of treatment success for substance dependence. Participants were 35 adults (27 men, 8 women) undergoing treatment for substance dependence at an urban residential treatment facility between October 2005 and July 2007. Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR) criteria were used to confirm substance dependence. P3a amplitude was significantly smaller for those who dropped out of treatment. Discriminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…It also corroborates the assertion of Pammer [18], who reported that structural changes in the brain are observed as consequences of phonological and reading intervention. In this way, this study confirms that P300 is a viable tool to measure and monitor neurophysiological modifications of the central auditory nervous system, corroborating the claims of Alonso and Schochat [26] and Anderson et al [27].…”
Section: P300 Auditory Cognitive Evoked Potential As a Tool For Monitsupporting
confidence: 77%
See 1 more Smart Citation
“…It also corroborates the assertion of Pammer [18], who reported that structural changes in the brain are observed as consequences of phonological and reading intervention. In this way, this study confirms that P300 is a viable tool to measure and monitor neurophysiological modifications of the central auditory nervous system, corroborating the claims of Alonso and Schochat [26] and Anderson et al [27].…”
Section: P300 Auditory Cognitive Evoked Potential As a Tool For Monitsupporting
confidence: 77%
“…The AEP is a cognitive potential generated by a complex neural network between the thalamus, temporal-parietal cortex, prefrontal cortex, and hippocampus region. In studying AEP, two components can be evaluated, the N2 (or N200), which is associated with the perception, discrimination, recognition, and classification of an auditory stimulus, and P3 (or P300), which occurs when the individual consciously recognizes the presence of a change in the auditory stimulus [26,27]. Also, it has been shown to be an effective tool in the objective evaluation of auditory attention in children with phonological deficits, short-term memory, and reading and writing alterations [28].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, CAEP-P300 use to assess neurophysiological changes that happened after the hearing training was seen in patients with hearing process disorder (10) , in cases of disfluency (12) , as well as a predictor of the results of chemical dependence treatment (11) . In this study, CAEP-P300 was analyzed in two moments, before and after the phonological remediation, associated with reading and writing.…”
Section: Discussionmentioning
confidence: 99%
“…The Cognitive Auditory Evoked Potential-P300 (CAEP-P300) has been used to measure and monitor neurophysiological modifications of the central auditory nervous system (10)(11)(12) . Also known as a potential associated with events, it is an endogenous potential elicited by auditory discrimination, when the subject reacts to rare stimuli randomly presented between frequent stimuli (Oddball paradigm) (13,14) .…”
Section: Introductionmentioning
confidence: 99%
“…In studies of substance abuse treatment completion with community samples, reduced P300 amplitude has been associated with treatment discontinuation and relapse (Bauer 1997, 2001a; Anderson et al. 2011). Reduced P300 amplitudes associated with treatment discontinuation and relapse are typically elicited during processing of task‐irrelevant distractor stimuli.…”
Section: Introductionmentioning
confidence: 99%